The Informant Questionnaire on Cognitive Decline in the Elderly : mean score at dementia diagnosis in Iceland - Thelma Haraldsdóttir 1993- (2021)
Dementia is thought to be the biggest challenge we face today when it comes to health and social care. The Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) is a common and widely used screening tool for dementia. The IQCODE has been used as a measure of cognitive decline in different cultures all over the world. The participants in this study were individuals going through dementia evaluation at the Memory Clinic at Landakot in 2017. The participants were 173, but after going through the data 39 participants were excluded due to missing IQCODE score, diagnosis or both. Of the remaining 134 participants, 72 (53.7%) were female and 62 (43.3%) were male. The age of the participants ranged from 50 to 91 years (M = 73.50, SD = 8.11). The participants were divided into three groups based on educational level. The neuropsychological tests and the IQCODE were examined to see if there were a significant difference between them. Results showed that the mean IQCODE score for all the participants was 3.78 (SD = 0.44). Women were being diagnosed younger, but there was a non-significant difference between the mean IQCODE score of men and women. Education was not found to have an effect on the outcome of the IQCODE. There was a non-significant difference between the IQCODE scores and the neuropsychological tests. Keywords: Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE), diagnosis, dementia, MCI Heilabilun er talin vera stærsta áskorunin sem við stöndum frammi fyrir í dag þegar kemur að heilsu og félagslegri ummönnun. The Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) er vel þekkt og mikið notað skimunartæki fyrir heilabilun. IQCODE hefur verið notað víða um allan heim í mismunandi menningarheimum. Þátttakendur þessarar rannsóknar voru einstaklingar sem fóru í gegnum taugasálfræðilegtmat á minnismóttökunni á Landakoti. Þátttakendur voru 173 en eftir að farið var í gegnum göngin voru 39 einstaklingar útilokaðir vegan þess að það vantaði IQCODE, greiningu eða bæði. ...